Pemenuhan Hak Atas Akses Informasi Lingkungan Hidup terhadap Pencemaran Udara DKI Jakarta - Akmal Haris; Rayhan Nizam Mahendra; Yazid An naufal (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Addressing air pollution in DKI Jakarta requires fulfilling the right to access environmental information, increasing public awareness, and fostering active participation as part of a holistic solution. Despite challenges in transparency of information and availability of data on air pollution, efforts have been made to improve accessibility of information for the public. Lack of awareness among the public about their rights to environmental information and low literacy rates pose barriers to increasing awareness. However, through advocacy campaigns, education, and providing training to the public, it is hoped that their awareness will improve. Active participation of the public in addressing air pollution can be enhanced through participatory forums and public consultation mechanisms. With the involvement of government, civil society organizations, the private sector, and the public at large, these efforts are expected to create a cleaner, healthier, and more sustainable environment for all residents of DKI Jakarta. In conclusion, fulfilling the right to access environmental information, increasing public awareness, and fostering active participation are key components in maintaining better air and environmental quality in densely populated urban areas like DKI Jakarta.